Viral sepsis is a complication in patients with Novel Corona Virus Disease (COVID-19) - Di Liu; Qiang Wang; Huacai Zhang; Li Cui; Feng Shen; Yong Chen; Jiali Sun; Lebin Gan; Jianhui Sun; Jun Wang; Jing Zhang; Qingli Cai; et al. (Elsevier, 2020)
Background: Until June 23th 2020, 9,195,635 laboratory-confirmed cases of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) infection have been reported worldwide, including 473,127 deaths. Bacterial infection is the main cause of sepsis, however, sepsis caused by virus is often ignored. Increased awareness, early recognition of viral sepsis, rapid administration of appropriate antiviral drugs, and urgent treatment can significantly reduce deaths of viral sepsis. Objectives: Given the rapid global spread of novel Corona Virus Disease (COVID-19), coupled with the high rate of missed diagnosis of viral sepsis caused by SARS-CoV-2 infection, it is urgent to evaluate the multiple organ failure score and viral sepsis in COVID-19 patients, so as to determine the clinical characteristics of viral sepsis more accurately and reveal the risk factors related to mortality. Methods: Here we provide a full description of three cases of viral sepsis and subsequent multiple organ dysfunction (MODS) caused by SARS-CoV-2 infection imported to Guiyang from Wuhan. Results: We analyzed complete laboratory examination, imaging data and treatment methods for the patients and assessed Sepsis-related Organ Failure Assessment score (SOFA score) and Multiple organ dysfunction scores (MOD score) daily, aimed to elucidate the clinical feature of viral sepsis and MODS and to attract enough attention by clinicians. Conclusions: Therefore, we strongly suggest to daily evaluate SOFA score and MOD score in severe and critically-ill COVID-19 patients, so as to early diagnose and prevention of sepsis and MODS.Given the rapid global spread of novel Corona Virus Disease (COVID-19), coupled with the high rate of missed diagnosis of viral sepsis caused by SARS-CoV-2 infection, it is urgent to evaluate the multiple organ failure score and viral sepsis in COVID-19 patients, so as to determine the clinical characteristics of viral sepsis more accurately and reveal the risk factors related to mortality. Here we provide a full description of three cases of viral sepsis and subsequent multiple organ dysfunction (MODS) caused by SARS-CoV-2 infection imported to Guiyang from Wuhan. We analyzed complete laboratory examination, imaging data and treatment methods for the patients and assessed Sepsis-related Organ Failure Assessment score (SOFA score) and Multiple organ dysfunction scores (MOD score) daily, aimed to elucidate the clinical feature of viral sepsis and MODS and to attract enough attention by clinicians. Therefore, we strongly suggest to daily evaluate SOFA score and MOD score in severe and critically-ill COVID-19 patients, so as to early diagnose and prevention of sepsis and MODS.